Impact of commercially popular machine mechanisms using simulation tool in computer-aided design for improvements in mechanical engineering curriculum. Issue 1 (December 2020) - Talli, Amit L; Hussien, Ahmed A.; Mohamed, Mazlan; Janvekar, Ayub Ahmed
Abstract: The main content in the kinematics of machinery course includes kinematic analysis of machines and mechanisms and forms an integral part of the mechanical engineering curriculum. The conventional way of teaching students about the machine mechanisms is either by lecture notes/PowerPoint presentations/blackboard sketches finds it challenging to get an overall concept. Students find it challenging to understand the movements of machine parts due to a lack of visualization. The course can be taught in much lucidly and persuasively way by physical models or virtual mechanisms in a software ecosystem. There are several commercial and free software exists that can be used to complement the teaching and learning. In this paper, more straightforward, and more intuitive CAD software is reported, which has a very simple to use interface and a swift learning curve. A user can appreciate why and how the mechanism works by simulation of various mechanisms through CAD software.